LARGE-SCALE LITHOSPHERIC STRESS FIELD AND TOPOGRAPHY INDUCED BY GLOBAL MANTLE CIRCULATION - Steinberger B.; Schmeling H.; Marquart G. (My University, 2001)
Stresses in the lithosphere are one indication of processes in the Earth interior: here we present a calculation of large-scale lithospheric stresses caused by global mantle circulation. The mantle flow field is calculated based on density structures inferred from global seismic tomography. Predicted principal stress directions are compared to interpolations based on observed stresses. Agreement between predictions and observations is often good in regions where lithospheric stresses and mantle tomography are well constrained. Predicted magnitudes of scalar stress anomalies vary more strongly than predicted stress directions for various tomographic models. Hotspots preferentially occur in regions where calculated stress anomalies are tensile or slightly compressive. Results do not strongly depend on radial mantle viscosity structure, lithospheric rheology (viscous or elastic) or plate motion model. The model also predicts the directions of motion well for most plates; misfits in the predicted magnitudes can be explained qualitatively. Stress anomalies due to causes within the lithosphere (oceanic cooling with age, variations in crustal thickness, topography isostatically compensated at subcrustal levels) are also computed. Predicted stress directions in the absence of mantle flow can explain observations almost as well as mantle flow. Nevertheless, current models of mantle flow are largely in accord with interpolations of observed principal stress directions and the observed plate motions.
Keywords: STRESS FIELDS; LITHOSPHERE; MANTLE; HOT SPOTS; PLATE TECTONICS